Lipid droplet-associated hydrolase mobilizes stores of liver X receptor sterol ligands and protects against atherosclerosis - Goo, Young-Hwa; Plakkal Ayyappan, Janeesh; Cheeran, Francis D.; Bangru, Sushant; Saha, Pradip K.; Baar, Paula; Schulz, Sabine; Lydic, Todd A.; Spengler, Bernhard; Wagner, Andreas H.; Kalsotra, Auinash; Yechoor, Vijay K.; et al. (Nature Communications, 2024)
Foam cells in atheroma are engorged with lipid droplets (LDs) that contain esters of regulatory lipids whose metabolism remains poorly understood. LD-associated hydrolase (LDAH) has a lipase structure and high affinity for LDs of foam cells. Using knockout and transgenic mice of both sexes, here we show that LDAH inhibits atherosclerosis development and promotes stable lesion architectures. Broad and targeted lipidomic analyzes of primary macrophages and comparative lipid profiling of atheroma identified a broad impact of LDAH on esterified sterols, including natural liver X receptor (LXR) sterol ligands. Transcriptomic analyzes coupled with rescue experiments show that LDAH modulates the expression of prototypical LXR targets and leads macrophages to a less inflammatory phenotype with a profibrotic gene signature. These studies underscore the role of LDs as reservoirs and metabolic hubs of bioactive lipids, and suggest that LDAH favorably modulates macrophage activation and protects against atherosclerosis via lipolytic mobilization of regulatory sterols.